2020
DOI: 10.3389/fonc.2020.520330
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Glucose to Lymphocyte Ratio (GLR) as a Prognostic Marker for Patients With Pancreatic Cancer

Abstract: Glucose metabolism and systemic inflammation have been associated with cancer aggressiveness and patient prognosis in various malignancies. This study aimed to evaluate the prognostic significance of pretreatment GLR(glucose to lymphocyte ratio) and systemic immune inflammation in patients with pancreatic cancer. We studied 360 patients with pathologically diagnosed pancreatic adenocarcinoma that was clinically unresectable. Baseline clinicopathological characteristics and laboratory investigations including f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 39 publications
0
38
0
Order By: Relevance
“…Cytotoxic CD8 + T cells (CTLs) are the primary lymphocytes for killing tumor cells. They secrete cytotoxic enzymes including perforin and granzyme, and can interact with the major histocompatibility complex I (MHC-I) ( Tanaka et al, 1999 ; Jackaman et al, 2012 ; Martínez-Lostao et al, 2015 ; Wei et al, 2018 ; Zhong et al, 2020 ). The involvement of CTLs in tumor therapeutic resistance is proven by the strong association between the profile of CTLs in tumors and the chemotherapy outcomes ( Figure 3 ) ( Denkert et al, 2010 ; Halama et al, 2011 ; Chen and Chang, 2019 ).…”
Section: Tme-driven Adaptive Mechanisms Of Therapy Resistancementioning
confidence: 99%
“…Cytotoxic CD8 + T cells (CTLs) are the primary lymphocytes for killing tumor cells. They secrete cytotoxic enzymes including perforin and granzyme, and can interact with the major histocompatibility complex I (MHC-I) ( Tanaka et al, 1999 ; Jackaman et al, 2012 ; Martínez-Lostao et al, 2015 ; Wei et al, 2018 ; Zhong et al, 2020 ). The involvement of CTLs in tumor therapeutic resistance is proven by the strong association between the profile of CTLs in tumors and the chemotherapy outcomes ( Figure 3 ) ( Denkert et al, 2010 ; Halama et al, 2011 ; Chen and Chang, 2019 ).…”
Section: Tme-driven Adaptive Mechanisms Of Therapy Resistancementioning
confidence: 99%
“…Another study indicated that GLR is associated with prognosis in pancreatic cancer patients. 25 Moreover, Navarro et al 26 revealed that GLR is a prognostic marker in patients with resected pT2 gallbladder cancer. As far as we know, the present study verified that GLR is an independent prognostic marker to predict outcome in critically ill patients with AP according to the results of multivariate Cox regression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…CAR and NLR are inflammatory response markers that effectively predict the prognosis in various cancers [13][14][15]. Zhong et al stated that GLR has an essential role in determining the prognosis in pancreatic cancer patients, and that GLR alone is more effective in determining the average overall survival than NLR and CAR [12]. In another study, CAR and NLR were shown to have strong prognostic predictive values for gastric cancer [16].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in the rate of glucose-lymphocyte ratio (GLR) due to hyperglycemia and immunosuppression is expected in cancer patients. The ratio of preoperative blood glucose level and lymphocyte counts significantly predicts prognosis in pancreatic cancers [12]. There is still a need for a more accurate and comprehensive assessment system with improved sensitivity and specificity for the assessment of prognosis.…”
Section: Introductionmentioning
confidence: 99%